Study of orbits on the finite projective plane. Issue 6 (17th August 2020) - Makhrib Al-Seraji, Najm Abdulzahra; Bakheet, Ahmed; Jafar, Zainab Sadiq
Abstract: The aims of this paper are to classify the group action on a projective plane PG(2, q ), when q 2 + q + 1 is not a prime, and then describe the geometry of these orbits with values of q = 43, 47, 49. Investigate partitions of PG(2, q ) with q = 49, into subgeometries PG(2, q ) when q = 7. Also establish codes and arcs with different degrees.